Green financing in India: identifying future scope for innovation in financial system. (12th February 2022) - Bhatnagar, Sumedha; Sharma, Dipti
Green financing (GF) is an approach through which countries can encourage economic growth in convergence with environment supportive activities through innovative development of the financial industry. The concept is in a very nascent stage in developing countries like India. The paper reviews the potential of GF in India by conducting SWOT analysis. The results of the study indicated that green financing in India is largely concentrated in the renewable energy sector followed by the construction and transportation sector. Green bonds, as a financial funding instrument, have the potential to grow in the domestic market and their low credit rating is the major obstacle to the development of the green bond market. The results obtained from the analysis also suggest that the development of GF requires an integrative approach of the government, financial system, policymakers, private sector and non-governmental organisations for market diversification and risk mitigation.